Characterization of 22 nm FDSOI nMOSFETs With Different Backplane Doping at Cryogenic Temperature - Tiantian Xie (IEEE, 2021)
In this work, the electrostatic and radio frequency performances of 22 nm FDSOI nMOSFETs with p-type or n-type doped backplane (BP, highly doped layer of silicon below thin buried oxide) at cryogenic temperatures have been investigated. Greater enhancement of drain current $\text{I}_{ d}$ , maximum transconductance $\text{g}_{ m,max}$ and threshold voltage $\text{V}_{ TH}$ values have been demonstrated at liquid nitrogen temperatures. Furthermore, FDSOI nMOSFETs with n-type BP achieve the maximum transconductance at lower bias voltage and smaller $\text{V}_{ ZTC}$ , which is mainly due to its small threshold voltage. The variation of threshold voltage of BP-p devices is greater with the decrease of temperature. About 40% improvement of $\text{f}_{ T}$ and 30% improvement of $\text{f}_{ max}$ depended on the $\text{W}_{ f}$ of devices have been shown. Relevant small-signal parameters (e.g., transconductance $\text{g}_{ m}$ , gate capacitance $\text{C}_{ gg}$ , gate resistance $\text{R}_{ g}$ and output conductance $\text{g}_{ ds}$ ) are also extracted for comparison and analysis. This study presents both 22 nm FDSOI nMOSFETs with p-type or n-type backplane as good candidates for cryogenic applications down to 77 K, and especially, BP-n FDSOI are more suitable for low power operation applications because of their lower threshold voltage. Similar $\text{g}_{ m.max}$ and the peak values of RF FOMs can be obtained at lower bias voltage compared with BP-p devices.